Optimalisasi Penggunaan Bahasa Indonesia dalam Pelayanan Publik di Lumbung Uti Asmoro, Kecamatan Limboto, Kabupaten Gorontalo, Gorontalo - Dali, Meilina Widya; Pratama, Muhammad Raditya; Samson, Deistia Amelia; Sumarkondi, Mohammad Devano; Dukalang, Tiara Tri Wardani; Prayoga, Rido Ade; Ibrahim, Siti Fadilla; Abdullah, Oirunisa; Usman, Ainun; Hasan, Nur Fadhila; Aulia, Aulia; Hamadi, Sarah Amalia; Sahrain, Nuraisya; Ramadhani, Myca Mitha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to identify the importance of optimizing the use of Indonesian in public services at the Lumbung Uti Asmoro tourist destination, Limboto District, Gorontalo Regency, Gorontalo. Indonesian as the national language has a strategic role in creating effective, professional, and ethical communication in public services, particularly in the tourism sector. This study uses a descriptive method with a qualitative approach. Data collection techniques were carried out through direct observation, semi-structured interviews, and documentation. Research informants consisted of the owner, employees, and visitors of Lumbung Uti Asmoro. The data obtained were analyzed by grouping information based on themes relevant to the use of Indonesian in public services. The results of the study indicate that the use of communicative Indonesian, although not yet fully standardized, is able to create effective interactions between service providers and visitors. Clear, polite, and easy-to-understand language increases visitor satisfaction, streamlines the service process, and builds a positive image of the tourist destination. Thus, optimizing the use of Indonesian in public services at Lumbung Uti Asmoro contributes significantly to the quality of service and visitors' tourism experience.